DIGITALISASI FINANCIAL STATEMENTS DAN PENILAIAN FINANCIAL PERFORMANCE PADA UMKM MEGATRILAND - Awanda Rachma Dhea Atyaningsih; Handayani Soedarso, Elvyra; Dwi Ernawati, Widi (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
This study aims to implement the digitalization of financial statements using Zahir Accounting and measure the financial performance (e.g., activity, profitability, liquidity, solvency) of Megatriland, a micro, small, and medium-sized enterprise (MSME). Primary data on ownership structure, industry sector, and business policies will be collected through semi-structured interviews with the owner. Additionally, secondary data analysis will be conducted on financial transaction records, such as financial statements. Zahir Accounting Software empowers Megatriland MSME to generate financial statements, including income statements, balance sheets, and cash flow statements, with greater accuracy and real-time functionality. Furthermore, through ratio analysis, the software streamlines financial performance monitoring by encompassing activity, liquidity, profitability, and solvency ratios. Zahir Accounting software empowers Megatriland MSME to manage finances more efficiently, potentially improving the quality of financial decision-making. This study's findings suggest that digital accounting technology can contribute to optimizing financial management at Megatriland MSME, potentially leading to improved performance and sustainability for micro, small, and medium-sized enterprises. Keywords: Financial Performance, Financial Statements, MSME, Zahir Accounting